Approach to a conceptual frame of technological perspectives for water resources management in the Mediterranean Region - Rabi A.; Martín Garcia I.; Mandi L.; Berbel J.; El Moujabber M.; Rodríguez-Clemente R.; Serneguet M. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
The 2nd Melia project workshop, held in Marrakech in November 2008, was intended to face the problem of freshwater availability in the Mediterranean region due to the growing demand. This often creates conflicts among the various sectors and places great pressure on the ecosystems supporting these resources. Most of these issues and the technological perspectives of sustainable integrated water resources management in the Mediterranean region was discussed, focusing on the technology used to enhance water supply, the preservation of resources quality, the social and cultural aspects of water management, the institutional, governance and policy aspects and emphasizing the importance of available technical tools to improve management (GIS and remote sensing). The debate also addressed the various regulations and directives in the field of resources management and the new challenges posed, particularly, by global and climate change, the changing world economy and social and economic disparity between Southern and Northern Mediterranean countries and the need for bridging this gap in order to promote sustainable management of resources in the Mediterranean Basin. As a result, some key concepts were defined and the final recommendations outlined a number of criteria to tailor technology to the sustainable management of scarce water resources in the Mediterranean region.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)